1971
DOI: 10.1063/1.1659996
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Charging of Thermal SiO2 Films by Injected Electron Currents

Abstract: When electron currents flow in thermal SiO2 films which have been exposed to water, a buildup of negative charge occurs in the oxide. This paper describes a series of experiments designed to characterize this charging effect. It is found that if water is diffused into a SiO2 film, water related centers are formed which act like electron traps with capture cross section of approximately 1.5 × 10−17 cm2. Experiments are described which show that when one of these centers captures an electron, atomic hydrogen is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
112
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(121 citation statements)
references
References 25 publications
9
112
0
Order By: Relevance
“…Multiple-reflection attenuated-total-reflection FTIR spectrometry (ATR-FTIR) have found evidence for electrochemical trapping of electrons by SiOH silanol groups on the SiO 2 substrate. 30,31 SiOH concentration on the SiO 2 surface has been determined to be ∼(3-7) × 10 13 cm -2 in a number of studies. 32,33 This concentration is nevertheless electronically significant, as it exceeds or is comparative to the typical carrier concentration of 10 13 cm -2 found recently in single Bi 2 Te 3 NP devices with a top gate and Bi 2 Te 3 nanoribbon based field-effect transistor (FET).…”
Section: Surface Potentials Of Bi 2 Te 3 Npsmentioning
confidence: 99%
“…Multiple-reflection attenuated-total-reflection FTIR spectrometry (ATR-FTIR) have found evidence for electrochemical trapping of electrons by SiOH silanol groups on the SiO 2 substrate. 30,31 SiOH concentration on the SiO 2 surface has been determined to be ∼(3-7) × 10 13 cm -2 in a number of studies. 32,33 This concentration is nevertheless electronically significant, as it exceeds or is comparative to the typical carrier concentration of 10 13 cm -2 found recently in single Bi 2 Te 3 NP devices with a top gate and Bi 2 Te 3 nanoribbon based field-effect transistor (FET).…”
Section: Surface Potentials Of Bi 2 Te 3 Npsmentioning
confidence: 99%
“…So far, the dominant electron traps have been associated with impurity-related centers, in particular, the hydrogen-related network fragments. [10][11][12][13] It has been well established that electrons can be trapped by Ge impurities substituting for Si in both α-quartz 14 and in a-SiO 2 15 with models of these centers recently revisited by Griscom. 16 A defect consisting of an extra electron trapped at a four-coordinated silicon atom and stabilized by an adjacent interstitial Li ion has been observed in quartz.…”
Section: Introductionmentioning
confidence: 99%
“…The SiO 2 thin film, which is thermally grown on highly n-doped Si (the fabrication method and properties are described in detail in Methods and the Supplementary Information), has a highly dielectric structure with minimal defects. Therefore, it permits both the selective migration of protons and the diffusion of electrogenerated H atoms 9 in the middle of the electrical potential gradient. This result suggests that H atoms in the EOS system could be used as electron mediators on dielectric oxide layers acting as 'chemical electrodes' for electrochemical reactions.…”
mentioning
confidence: 99%
“…In this work, we introduced thermally grown silicon dioxide (SiO 2 ), a dense and stable dielectric layer, and explored the novel phenomena that could be observed in this electrochemical system. Thermal SiO 2 is a dielectric material used for conventional metal/insulator/metal capacitors 6 , and SiO 2 films are widely used as gate insulators of metal/oxide/semiconductor (MOS) devices 7 , in which the field-induced drift of protons to the Si/SiO 2 interface and their interactions with electrons can create hydrogen (H) atoms at the interface 8,9 . Shkrob et al 10 demonstrated that protons were reduced to generate mobile H atoms in B 2 O 3 glasses at room temperature.…”
mentioning
confidence: 99%